Increased Interest in Reading and Writing in Students of SB Kampung Bharu Kuala Lumpur Malaysia through Image Media - Agus Rohmat Hidayat; Aldo Hermaya Aditiya Nur Karsa; Septien Dwi Savandha (Syntax Idea)
The purpose of this study was to determine the increase in reading and writing interest of Sanggar Bimbingan (SB) students of Kampung Bharu, Kuala Lumpur, Malaysia through visual media. This study used descriptive research methods, specifically using classroom action research. This approach includes four distinct stages: planning, execution, observation, and reflection. The study involved a sample size of 10 students. The results of data analysis in cycle 1 showed that children developed interest in reading and writing with the picture method reaching 58% to 72%, while in cycle 2 of meetings 1 and 2 the level of interest increased. In reading, writing and counting using visual methods. Reached 95.4%. This shows that the teacher's actions are good.